"Evaluación del proceso fermentativo de la madarina king (Citrus nobillis L.) aplicando benotonita, albumina y pectinasa para su clarificacion" - Pinargote Mendoza, Angela María (2016)
ABSTRACT In this research, a fermented drink made of the king mandarin, applying bentonite, albumen and pectinase for clarification was made. The main problem in this study was turbidity and color, which could generate the same consumer rejection. The overall objective of this research was to analyze the conditioning of the must (juice with pulp and juice without pulp) and determine which of the three clarifiers (bentonite, albumen and pectinase) best acts in the clarification stage resulting in a product low in turbidity albumin applied drink and pectinase and other haze because not all clarifiers not act in the same way. The raw material was obtained from the estate of the Fernandez family in the Parish Moraspungo Cotopaxi Province. Selected mandarins was used for the preparation, we proceeded to washing / disinfection after juice extraction is performed. For fifteen days fermentation in which after some time has elapsed the three types of fining was added was performed. For maturation she was allowed to stand for two months at room temperature. Thus achieve the sugars, acids and alcohols are mixed with each other giving the product its odor, color, flavor and aroma characteristic of the fermented drink tangerine. The experimental design was a factorial Completely Randomized Block A * B * analysis of variance for each variable, 6 treatments with 3 replications for a total of 18 units were determined. Chemicals Physical sensory analysis was performed as best treatment was a1b1 (juice without pulp * Albumin) obtaining a fermented drink .The results show that by applying Albumin acts favorably for clarification in the process of obtaining the fermented drink mandarina .